PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PUNGUTAN LIAR YANG DILAKUKAN OLEH PEGAWAI NEGERI SIPIL DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN ATAS UNDANG- UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Debby Diannita Jaya; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Illegal charges are those committed by a person or a Civil Servant or a State Official by requiring payment of an unsuitable amount of money based on regulations relating to the payment. This is often equated with extortion, fraud or corruption. In practice, Illegal charges have been regulated in Law No. 20 of 2001 on Amendment to Law Number 31 Year 1999 on Corruption Eradication. In reality, however, the crime of illegal levies is still prevalent in the various services performed by civil servants. One of them in the Department of Population and Civil Registration of Pekanbaru City. This illegal levy certainly required a very firm law enforcement to be overcome maximally. But the action of this Illegal charges still occur with various opportunities that exist. The problems and objectives to be discussed in this thesis is to know how the form of law enforcement against the perpetrators of illegal charges committed by civil servants in the city of Pekanbaru based on Law No. 20 of 2001 on the amendment of Law No. 31 of 1999 on the eradication criminal act of corruption.This type of research is sociological, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at Pekanbaru Town Police Department and Population and Civil Registration Office of Pekanbaru City, while population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection in this study with interviews, questionnaires and literature study.The result of the research can be concluded that Law Enforcement on illegal charges conducted by civil servants in Pekanbaru city has not run well and maximum. The constraints faced cause law enforcement of these illegal fees to be low and difficult to implement maximally. To overcome this problem, it is suggested to tighten the supervision on illegal fees and also to socialize to the public so that the public will be more understanding about the criminal sanction of Illegal charges.Kata kunci : Law Enforcement - Illegal Charges - Civil Servants - Corruption